Triple Arthrodesis for Equinovarus Foot using Ilizarov Technique: A Retrospective Study - RITESH ARVIND PANDEY (JCDR Research and Publications Private Limited, 2021)
Introduction: Equinovarus foot deformity is a significant problem in adolescents and its treatment remains challenging. Triple arthrodesis, even though an effective palliative tool in management of complex foot deformity, has its own limitations if it is done for acute deformity correction. Ilizarov technique offers gradual deformity correction, fusion and takes care of many known complications of acute correction. However, there are very few studies about effectiveness and functional outcome of triple arthrodesis for equinovarus deformity when done gradually with an Ilizarov fixator. Aim: To study the effectiveness of triple arthrodesis, performed with Ilizarov technique for equinovarus foot deformity in adolescents and adults and to evaluate the early functional outcome and patient satisfaction rate for this procedure. Materials and Methods: A retrospective analysis of 22 feet in 20 patients with equinovarus foot deformity between January 2015 and December 2018 was done. Patients underwent gradual deformity correction and triple fusion with Ilizarov fixator. Foot was assessed for any residual deformity and shortening. Functional outcome and patient satisfaction were assessed by Ankle Hind Foot Scale (AHFS) and Likert scale, respectively using paired t-test. Final analysis was done with Statistical Package for Social Sciences (SPSS) software version 21.0. Results: Twelve males and eight females with mean age of 15.9±3.4 years fulfilled the inclusion criteria and were included for final analysis of results. Fusion rate was 86.1% with mean union time of 12.5 weeks. Mean AHFS improved from 61.27 before surgery to 76.9 which was statistically significant (p<0.0001). One or more complications were seen in 15 (68.1%) feet but were managed satisfactorily without any significant impact on final outcome. Patient satisfaction rate for the procedure was 80%. After a mean follow-up of 18.1 months, plantigrade foot with equal foot length was obtained in all patients. Conclusion: Triple arthrodesis with gradual deformity correction by Ilizarov technique effectively corrects equinovarus foot deformity and foot length discrepancy. Known complications of acute deformity correction can be avoided with equally good results. It corrects deformity and restores alignment of foot more accurately leading to a high patient satisfaction rate.